O Camisa 10 em campo: elementos do processo de formação de um futebolista brasileiro - Oliveira, Flávio Ismael da Silva [UNESP] (2014)
This research aimed to understand the formative process of soccer player Arthur Antunes Coimbra - Zico. In the condition of a qualitative research, guided by the oral history, and present and contemporary history approaches, we analyzed his experiences and perspectives in search of evidences that enabled us to understand decisive relations to his formation. Different from the current configurations, that ensured the involvement of Zico with footballs and their variations favored a range of significant experiences in the most varied environments. For many years this context prevailed, however, over the years these paths change and become more complex, extensive, exhaustive, expensive, competitive and systematic. The complexity of the process leads us to believe that the initial formative process of the soccer player is under strong contextual influence, including: family, peers, experiences, institutions, professional intervention, teaching and training methodologies, competitive system, awards and many other contexts that comprise formal and informal environments. Considering that soccer today is different from a few decades, and the cultural importance remains so solid in Brazil, we are convinced that training centers must rearrange to respond positively to current and future demands of soccer. Methodologies and tools used in the identification and development of professional soccer players must be reconsidered. By the current context, we believe that the configurations that permeate the formative process leads us to adopt a cautious attitude regarding the possibility emergence of soccer players with the same distinction of Zico and more frequently. Therefore, the formation process can be compromised putting at risk the symbolic prominent position Brazil has on the international sports scene, as one of the leading countries in formation of soccer players